Nanometric displacements measurement in piezoelectric polymers using bivariate empirical mode decomposition method in speckle patterns - Pablo Etchepareborda; Francisco Veiras; Arturo Bianchetti; Alejandro Federico; Martin German Gonzalez (Revista Elektrón, 2019)
In this work we present an optical method for the direct determination of the piezoelectric coefficient of polymeric thin films. This is achieved through the measurement of nanometric mechanical displacements generated in the film when it is excited by low frequency harmonic electrical signals (0.5 Hz). The system is based on the temporal speckle pattern interferometry technique and the recovery of phase by using a bivariate empirical mode decomposition framework. The experimental scheme was used on a sample of vinylidene polyfluoride deposited on a glass substrate. The sample presents similar conditions to those found in the characterization of complex fluids by photoacoustic techniques. The measured value agrees with those obtained by other methods and with the value reported by the manufacturer.